Path Analysis to Determine the Relationship Between Marital Dissatisfaction, Premenstrual Syndrome and Emotional Dimension of Quality of Life in Women - Zohreh Karimian Kakolaki; seyed saeed Mazloomy mohmoodabad; Sakineh Gerayllo; Fatemeh Heidari; Bahareh Motaghi; Firoozeh Sharifi (Journal of Community Health Research, 2018)
Introduction: Marital satisfaction was defined as individuals’ global subjective evaluation of the quality of their marriage. Quality of life (QOL) is a multidimensional concept and includes all aspects of individuals’ lives. Premenstrual syndrome (PMS) is characterized by a wide variety of emotional and physical symptoms and behavioral changes. The purpose of this study was to determine the role of marital dissatisfaction and premenstrual syndrome in the emotional dimension of quality of life.   Methods: This study was analytical cross-sectional.  246 women referred to health centers in the border Yazd city, were recruited, voluntarily or accidentally. Tools for data collection were Quality of life questionnaire SF36, Premenstrual Syndrome Screening Tool and Index of Marital Satisfaction(QOL &PSST & IMS). Data collected was coded by SPSS18, descriptive statistics were used to summarize and organize the data and analyzed with path analyze Test. Results: Marital dissatisfaction (p = 0.021) and premenstrual syndrome (p = 0.001) have a direct negative effect on the quality of life's emotional dimension, and the severity of premenstrual syndrome has a stronger effect. Also, marital dissatisfaction with the effect on the severity of premenstrual syndrome (p = 0.001) indirectly affects the quality of life's emotional dimension. Conclusions: The findings of this study emphasize that women with premenstrual syndrome and marital dissatisfaction have a problem in their emotional dimension, so women should be taught that, in order to have a better mental health, to overcome Complications of marital life and recognizing the symptoms of premenstrual syndrome and its improvement strategies will further control these factors and increase their quality of life.